Excitons - Pyshkin, Sergei L. (IntechOpen, 2018)
Excitons, as part of the InTech collection of international works on optics and optoelectronics, contains recent achievements of specialists from China, France, Japan, Switzerland, and Moldova jointly with Russia and the United States of America on properties and application of excitons in electronics. The growing number of countries participating in this endeavor and joint participation of the US, Moldova, Italy, and Russian scientists in investigations of excitons in the edition of this book testify to the unifying effect of science. An interested reader will find in the book the description of properties and possible applications of excitons, as well as the methods of fabrication and analysis of operation and the regions of application of modern excitonic devices.